Ozolife Softgels®, New alternative in the treatment of Helicobacter pylori (Ozone Therapy Global Journal, 2016)
There are multiple treatments to eradicate Helicobacter pylori. However, the infection caused by it is a problem not yet resolved. According to existing schemes, the resistance rates keep on increasing. Globally, the standard triple therapy has lost the efficacy that had in the past and the sequential therapy is not equally effective on all sites. For these reasons, we took advantage of the biological effects of ozonated oils and conducted this trial. The experimental design included 48 patients with positive diagnosis for H pylori (Respiratory urease test and Antigen fecal test) and treated them with soft capsules (Ozolife Softgels®) made of ozonized sunflower oil with peroxide index of 500 mEqO2/kg. The softgels were given to the patients 3 times a day for 30 days. At the end of the treatment the diagnosis test was repeated and a new cycle of treatment was performed to patients who continued to have a positive test.The results of the study in terms of eradication (> 93%) of H. pylori were similar to the efficacy of triple standard antibiotic therapy (~80%). In addition, it has huge advantages in terms of the absence of collateral symptoms and antimicrobial resistance Therefore, Ozolife Softgels® is considered an alternative in the treatment of H. pylori infection and symptoms that accompany it, such as heartburn, chronic gastritis and peptic ulcer.